1984
DOI: 10.1111/j.1095-8339.1984.tb01567.x
|View full text |Cite
|
Sign up to set email alerts
|

Some observations on the structure, cation content and possible evolutionary status of dinoflagellate chromosomes

Abstract: SICEE, D. C., 1984. Some observations on the structure, cation content and possible evolutionary status of dinoflagellate chromosomes. Dinoflagellate chromosomes have a well‐ordered structure, as observed in living cells, glutaraldehyde/osmium tetroxide‐fixed cells, ultrathin cryosections and freeze‐etch preparations. It is suggested that the stabilization of this chromatin in the living cell is largely mediated by divalent cations, acting as bridging molecules between the DNA superstructure and the protein ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Iron occurring as a component of dinoflagellate chromatin (Sigee 1984) represents at least one non-catalytic iron requirement unique among other algae and higher Doucette and P.J. Harrison: Dinoflagellate Fe and N nutrition.…”
Section: T Weissflogiimentioning
confidence: 99%
“…Iron occurring as a component of dinoflagellate chromatin (Sigee 1984) represents at least one non-catalytic iron requirement unique among other algae and higher Doucette and P.J. Harrison: Dinoflagellate Fe and N nutrition.…”
Section: T Weissflogiimentioning
confidence: 99%
“…As the properties of these threads are very similar to the chromosomes they are originating from, we believe that they represent a chromatin intermediate unfolding state. Previous studies suggested that DNA structures protruding from the chromosome core have a role in RNA transcription ( Rizzo, 1991 ; Sigee, 1983 , 1984 ; Soyer-Gobillard et al, 1990 ). Such structures, originating from the chromosomes and branching towards the nucleoplasm, have been reported in various dinoflagellate species ( Bhaud et al, 2000 ; Decelle et al, 2021 ; Soyer-Gobillard et al, 1990 ).…”
Section: Discussionmentioning
confidence: 99%
“…1A and B), with a maximum unwinding corresponding with the peak of replication in S phase (Spector et al, 1981;Costas and Goyanes, 2005). They are attached to the nuclear envelope and have a unique organization (Sigee, 1984a;Dodge, 1985;Rizzo, 1991). Free-living dinoflagellates have high chromosome numbers per haploid genome (20-270) (compare Fig.…”
Section: Characteristics Of Dinoflagellate Chromosomesmentioning
confidence: 99%